2023
DOI: 10.1108/itp-02-2022-0122
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement of online car-hailing drivers: the effects of platforms' algorithmic management

Abstract: PurposeAlgorithms are widely used to manage various activities in the gig economy. Online car-hailing platforms, such as Uber and Lyft, are exemplary embodiments of such algorithmic management, where drivers are managed by algorithms for task allocation, work monitoring and performance evaluation. Despite employing substantially, the platforms face the challenge of maintaining and fostering drivers' work engagement. Thus, this study aims to examine how the algorithmic management of online car-hailing platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…Initially proffered by Webster et al [ 16 ], Searle and Auton [ 17 ] subsequently validated new measures of challenge and hindrance appraisals, showcasing their utility in stress research and articulating a distinct CHAF. Many empirical studies have since adopted this framework to explore the effects of AI [ 18 , 19 ], algorithm management [ 12 , 20 ], employee demands [ 21 , 22 , 23 ] and other factors on workers’ behaviors and intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially proffered by Webster et al [ 16 ], Searle and Auton [ 17 ] subsequently validated new measures of challenge and hindrance appraisals, showcasing their utility in stress research and articulating a distinct CHAF. Many empirical studies have since adopted this framework to explore the effects of AI [ 18 , 19 ], algorithm management [ 12 , 20 ], employee demands [ 21 , 22 , 23 ] and other factors on workers’ behaviors and intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To address the posited research questions and ameliorate the identified research gap, this study strategically amalgamates the affective events theory with the challenge–hindrance appraisal framework (CHAF) and the conceptualization of prosocial service behaviors (PSBs), thereby guiding the formulation of the theoretical model. In examining the impact of challenge–hindrance appraisals on PSBs, work engagement (WE) is selected as the mediator, given its previously established status as an antecedent of PSBs and an outcome of challenge–hindrance appraisals [ 11 , 12 ], thereby showcasing its appropriateness as a mediator between challenge–hindrance appraisals and PSBs. Moreover, delving into potential contingencies that shape the relationship between multifarious factors and gig workers’ behaviors is imperative.…”
Section: Introductionmentioning
confidence: 99%